2013
DOI: 10.1038/srep01462
|View full text |Cite|
|
Sign up to set email alerts
|

A novel human endogenous retroviral protein inhibits cell-cell fusion

Abstract: While common in viral infections and neoplasia, spontaneous cell-cell fusion, or syncytialization, is quite restricted in healthy tissues. Such fusion is essential to human placental development, where interactions between trophoblast-specific human endogenous retroviral (HERV) envelope proteins, called syncytins, and their widely-distributed cell surface receptors are centrally involved. We have identified the first host cell-encoded protein that inhibits cell fusion in mammals. Like the syncytins, this prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 43 publications
2
105
1
1
Order By: Relevance
“…In contrast, another ERV transcript, ERVH48-1, is depleted in SCTBs (Fig. 2B), concordant with a recent report that it functions as an inhibitor of syncytium formation in VCTBs (35). To further study the cell fusion process, we identified genes that showed variation similar to ERVFRD-1 along the SCTB pathway (Fig.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, another ERV transcript, ERVH48-1, is depleted in SCTBs (Fig. 2B), concordant with a recent report that it functions as an inhibitor of syncytium formation in VCTBs (35). To further study the cell fusion process, we identified genes that showed variation similar to ERVFRD-1 along the SCTB pathway (Fig.…”
Section: Resultssupporting
confidence: 87%
“…ERVFRD-1 has been proposed to be immunosuppressive, an activity not shared by ERVW-1 (Mangeney, et al 2007). Several other ERV proteins, e.g.ERV3-1, and ERVK family members, including an antagonist of cell fusion (Sugimoto, et al 2013) are expressed in the placenta, but roles for most are even more obscure than that of ERVFRD-1.…”
Section: Evolution Of Placenta Specific Genesmentioning
confidence: 99%
“…Given this hypomethylation of LTRs in placentas, it is not surprising that numerous sub-families of ERV proviruses are expressed within human placental tissues. More specifically, there is evidence of proviral transcription from ERV-E (Yi and Kim, 2007), ERV3 (ERV-R; Boyd et al, 1993; Andersson et al, 2005), ERV-K (Kammerer et al, 2011), ERV-fb1 (Sugimoto et al, 2013), ERV-V1/2 (Esnault et al, 2013), ERV-W (Blond et al, 2000), and ERV-FRD (Blaise et al, 2003; Supplementary Tables 1, 2). …”
Section: Ervs In the Placentamentioning
confidence: 99%